Accessing vs sourcing knowledge: A comparative study of R&D internationalization between emerging and advanced economy firms - Awate, Snehal; Larsen, Marcus M; Mudambi, Ram (Journal of International Business Studies, 2015)
Research and development (R&D) internationalization is on the rise for advanced economy multinationals (AMNEs) as well as emerging economy multinationals (EMNEs). We study EMNE R&D internationalization by comparing it to that by AMNEs in the context of an emerging, knowledge-intensive industry. We find that these two are fundamentally different processes. While the internationalization of AMNEs’ R&D activities can largely be explained in terms of the twin strategies of competence exploitation and competence creation, EMNE R&D internationalization is rooted in the firms’ overall catch up strategy to get on par with industry leaders. An in-depth comparison of knowledge flows reveals that within AMNEs, headquarters often serves the primary source of knowledge for R&D subsidiaries. In contrast, within EMNEs, headquarters accesses knowledge from R&D subsidiaries in advanced economies for innovation catch-up. Within this dichotomy, the innovative capabilities of EMNE headquarters develop more slowly and with greater difficulty than those of AMNE subsidiaries.